La violación de la propiedad privada por el uso de drones sin autorización del propietario - Alcívar Velasco, Gabriela Andrea (2025)
Given the advancement of technology, the use of drones acquired easily today becomes a reality in terms of the violation of personal and family privacy of citizens when drone users invade the private property of individuals, The lack of criminalization of the individual use of these objects does not allow to comply with what the Constitution of the Republic protects, that is, the right to privacy, so before the present scientific article it has been verified before the respective analysis that the Constitutional and international regulations that the right to private property for the protection of personal and family privacy is protected, However, the lack of the respective regulation in criminal law puts at risk the aforementioned rights by the improper use of drones, the present investigation adopted the documentary in which covers doctrine, jurisprudence and regulations both international and national, with its purely qualitative approach, with research methods of analysis, inductive-deductive, among others, with the objective of determining that there is a violation of the constitutional principle of the right to privacy due to the lack of criminalization of the misuse of drones, and as a result leave this work as a source of consultation and clear doubts and guide in solutions regarding the use of these objects.